Preparation and characterization of in situ entrapment of laccase in silica microparticles via an ambient drying procedure - Mansor, Azmi Fadziyana (Springer Netherlands, 2015)
A simple and reproducible method for in situ entrapment of laccase in silica microparticles was studied which involved hydrolysis and condensation of tetraethyl orthosilicate via sol–gel route using one-step (base catalyst) and two-step (acid–base catalyst) methods followed by an ambient drying procedure. The influence of method used, starting material compositions, and aging conditions toward polymeric structure and catalytic activity of the laccase entrapped silica microparticles (LSMs) were investigated. It was found that one-step method is not suitable for in situ entrapment purpose since it left significant amount of untrapped laccase in the reaction media and lead to laccase inactivation due to its active site alteration by continuous contact with basic condition. Conversely, the laccase was entirely entrapped in the silica matrices synthesized using the two-step method with the highest specific activity of 434.71 U/g obtained for the immobilized laccase. In addition, the LSM showed stability improvement toward pH and temperature compared to the free laccase and was able to retain more than 80 % of their initial catalytic activity after 1 month of storage duration. The treatment of the LSM with trimethylchlorosilane resulted in the increase in the surface hydrophobic properties which is expected to be useful for applications in nonaqueous medium.